Synthesis and characterization of N-alkyl-2-aminopyridinum oligomers as pour point depressants for crude oil - Eid M.S. Azzam; Sayed A. Ahmed; Hanafy M. Abd El-Salam; Osama A. Abd Allha; Elshafie A.M. Gad (Egyptian Journal of Petroleum)
The synthesis of N-decyl- (C10P), N-dodecyl- (C12P) and N-cetyl-2-aminopyridinum (C16P) oligomers was achieved by oxidative polymerization of N-decyl- (C10), N-dodecyl- (C12) and N-cetyl-2-aminopyridinium bromide monomers respectively in aqueous acid medium. Density function theory (DFT) was applied to recognize the reactive center in monomers used. The result of quantum calculations indicated that the oligomerization could proceed via open ring reaction. The obtained oligomers were characterized using FTIR and 1H NMR spectroscopy. In addition, the XRD and SEM were used to investigate the morphology of the prepared oligomers. The thermal stability of the obtained oligomers was followed by thermogravimetric analysis (TGA). The conversion of these oligomers is ranged from 61 to 68% and the weight average molecular weights are closed to 3000 g mol−1. The surface tension of the synthesized oligomers was measured at different concentrations and temperatures. The efficiency of the synthesized oligomers in depressing the pour point of crude oil was investigated. The synthesized oligomers showed high efficiency as pour point dispersants. Keywords: N-alkyl-2-aminopyridinum, Oligomers, Crude oil, Pour point dispersants